Buoyancy on the bayou : shrimpers face the rising tide of globalization - Harrison, Jill Ann, 1977- (ILR Press, 2012)
While shrimp-loving consumers have benefited from the lower cost of shrimp, domestic shrimp farmers have suffered, particularly in Louisiana. Jill Ann Harrison portrays the struggles that Louisiana shrimp fishers endure to remain afloat in an industry beset by globalization.